Kinetics of suspended solids removal in tube settler - Lekhak, Basant; Amatya, Iswar Man (Journal of Innovations in Engineering Education, 2021)
Water treatment plant plays a principal role for the purification and supplying of the potable water. Several modifications were made in the conventional sedimentation tank to improve its efficiency as a results of which concept of tube settler was developed. Tube settler is commonly used due to less detention time of about less than 15 minutes. The present study is aimed to highlight the performance of tube settler unit. The tube settler installed in the Siddhipur Water Treatment Plant (SWTP) was selected and detailed study was conducted. The kinetics of suspended solids removal was obtained from the turbidity removal mechanism at various flow rates. Evaluation of tube settler was conducted for three discharges viz., 7, 8.5 and 10 litre per seconds (lps). Removal efficiency of tube settler was evaluated by measuring the turbidity at various turbidity ranges and flows. For influent turbidity of 4 – 93, 4 – 97 and 2 – 89 NTU, the effluent turbidity was found to be 2 – 41, 2 -49 and 1 - 45 NTU at 7 lps, 8.5 lps and 10 lps respectively. The average turbidity removed at 7 lps, 8.5 lps and 10 lps were found to be 17.1769 NTU (48.482% of influent turbidity), 15.57 NTU (47.097% of influent turbidity) and 14.85 NTU (45.348% of influent turbidity) respectively. Increasing the flow rate from 7 lps to 10 lps decrease the removal efficiency from 48.482 to 45.348 %. This indicates the effectiveness of the tube settler. The maximum effluent turbidity of tube settler was found more than WHO and NWDQS guidelines, however, the slow sand filter installed operated after the removal of turbidity by the tube settler brought the effluent turbidity within the limit i.e., 5 NTU. Also the results indicated that, in the suspended solids removal mechanism of tube settler in terms of average efficiency of turbidity removal it was found to be more for low flow rates and low for high flow rates, however, their effectiveness in removing suspended solid concentration at any flow rates is uncompromised.